Advances in nutritional supplementation for sarcopenia management - Liu, Simin; Zhang, Lin; Li, Shuangqing (Frontiers in Nutrition, 2023)
Sarcopenia is a syndrome characterized by a decline in muscular mass, strength, and function with advancing age. The risk of falls, fragility, hospitalization, and death is considerably increased in the senior population due to sarcopenia.Although there is no conclusive evidence for drug treatment, resistance training has been unanimously recognized as a first-line treatment for managing sarcopenia, and numerous studies have also pointed to the combination of nutritional supplementation and resistance training as a more effective intervention to improve quality of life for people with sarcopenia. People with both malnutrition and sarcopenia have a higher mortality rate, so identifying people at risk of malnutrition and intervening early is extremely important to avoid sarcopenia and its associated problems. This article provides important information for dietary interventions in sarcopenia by summarizing the discoveries and developments of nutritional supplements such as protein, leucine, β-hydroxy-β-methylbutyric acid, vitamin D, vitamin C, vitamin E, omega-3 fatty acids, creatine, inorganic nitrate, probiotics, minerals, collagen peptides and polyphenols in the management of sarcopenia.